An experimental investigation on water penetration in the process of water assisted injection molding of polypropylene - Ahmadzai, A. Z.; Vesh, A. H. B. (Polimery, 2022)
The water penetration phenomenon in the process of water assisted injection molding (WAIM) of a semi-crystalline polymer i.e. polypropylene (PP) was investigated. WAIM has been developed for production of hollow plastic elements and for parts having separate internal void spaces or channels. It offers a cost-effective means of producing the large elements having a good surface finish, reduced weight, and relatively short cycle time. In this study three processing parameters were investigated, namely, water injection delay time, holding time and mold temperature. Their effects on water penetration length, part hollow core characteristic (e.g. wall thickness, core diameter) and shrinkage were explored. The mold cavity shaped a branched pipe (two-head) to be cored out via water penetration. The results indicated that an optimum product, namely, having longer water penetration, lower wall thickness difference, more uniform pipe diameter and low shrinkage could be produced at a higher holding time, a higher mold temperature and at an optimum delay time.